A process-dissociation analysis of semantic illusions - Mata, André; Ferreira, Mário B.; Reis, Joana (Acta psychologica, 2013)
We examine semantic illusions from a dual-process perspective according to which the processes that go into failing or succeeding to detect such illusions can be decomposed into controlled processes (checking the facts in the sentence against the information in memory) and automatic processes (the impression of truth that comes from the semantic associations between the elements in the sentence). These processes, we argue, make largely independent contributions to truth judgments about semantic-illusory sentences. The Process Dissociation Procedure was used to obtain estimates of these two kinds of processes. In Study 1, participants judged whether sentences were true or false while under high or low cognitive load. Cognitive load increased the rate of semantic illusions by specifically affecting controlled processing but not automatic processing. In Study 2, a previous paired-associate learning task also increased the rate of semantic illusions, but it did so by specifically affecting automatic processing, not controlled processing.